The response patterns of community traits of N2O emission-related functional guilds to temperature across different arable soils under inorganic fertilization. (May 2017) - Yin, Chang; Fan, Fenliang; Song, Alin; Fan, Xiaoping; Ding, Hong; Ran, Wei; Qiu, Huizhen; Liang, Yongchao
Abstract: Temperature is an important factor governing the community traits of N2 O-emission related functional guilds (mainly autotrophic ammonia oxidizers and heterotrophic denitrifiers) and their activities. However, there have been few attempts to explore the broad response patterns of these guilds to temperature changes across arable soils. For this, a temperature-controlled (15, 25 and 35 °C) microcosm experiment was conducted using three arable soils (Fujian, Gansu, and Jiangsu) in China under two different fertilizations (no fertilization control (CK) and inorganic fertilization (NPK)). In conjunction with the measurement of N2 O emission, the community structure and abundance of ammonia oxidizing archaea (AOA) and bacteria (AOB), as well as nirS - and nirK -denitrifiers were assessed using T-RFLP and quantitative PCR, respectively. The analysis of community traits indicated a consistent response pattern of AOAs to temperature in terms of guild abundance, and a consistent effect of inorganic fertilization on the abundance of AOBs, but soil-dependent response patterns to fertilization and temperature were found for nirS - and nirK -denitrifiers in terms of abundance and community structure. The correlation analysis suggested that AOAs possibly assumed a role in N2 O emission in all the tested soils, and nirS -denitrifiers probably participated in N2 O emission in both the Fujian and Gansu soil, while a considerable amount of N2 O emission in the Jiangsu soil might have been derived from heterotrophic nitrification. Highlights: A consistent response pattern of AOAs' abundance to temperature across three arable soils. A consistent response pattern of AOBs' abundance to inorganic fertilization across three arable soils. AOA possibly played an important role in the N2 O emission in all the tested soils. Heterotrophic nitrification might have considerably contributed to the N2 O emission in one of the tested soils.